Indonesian Journal of Physical Medicine and Rehabilitation - Luh Karunia (Indonesian Journal of Physical Medicine & Rehabilitation, 2012)
Three decades have passed by that Physical Medicine and Rehabilitation has beenexisting in Indonesia. In this time many improvements in professional practice andeducation have been achieved . Indonesian physiatrists have been developing skillsand knowledge regarding evidence-based medicine which is a standard of clinicalpractices. In line with that , many researches have been conducted all over our countryespecially in the educational centers of Indonesia.We are going to enrich and support other researches’ results conducted worldwideto strengthen evidences proofs by the internationally publication of Indonesianresearches. Other country may have other characteristic of population which couldbe different in demography, common diseases and disabling causes. This will give usall a better world understanding so as to progress in a forward direction in our mutualresearching.